Peningkatan Kapasitas Pengelola Homestay dan Pondok Wisata Melalui Pemasaran Digital dan Strategi Branding di Bintan - Hetty Yulianti Sihite; Indah Andesta; Firman Wahyu Illahi; Fitriana Baitanu; Nensi Lapotulo (Yayasan Literasi Sains Indonesia, 2025)
This community service program aims to enhance the capacity of homestay and guesthouse managers in Bintan Island, Riau Islands Province, in utilizing digital marketing and branding strategies to strengthen the competitiveness of community-based tourism enterprises. The program was conducted using participatory and applicative approaches through a two-day training held on 5–6 November 2025, involving 40 participants consisting of homestay managers, guesthouse operators, and local tourism practitioners. The training materials focused on three main topics: social media and Online Travel Agent (OTA) promotion, photo and video–based visual storytelling, and branding strategies for building business image and online reputation. Evaluation results indicate a significant improvement in participants’ knowledge and skills, with an average post-training score of 3.75 (categorized as good to very good). Participants were able to apply digital marketing techniques more effectively, produce engaging and authentic visual content, and manage their online image and reputation more professionally. The program also strengthened participants’ digital literacy and branding capabilities, while fostering a collaborative network among homestay managers for promoting community-based tourism in Bintan Island. Overall, this training contributes positively to enhancing the competitiveness of local homestays and supports the development of sustainable, technology-driven tourism in the region.